GreenlightTestPrep wrote:
Explanation
If f(–x) = –f(x) for all numbers x, then let's see what happens with some arbitrary value of x.
Let x = 2.
The correct answer will be such that f(-2) = -f(2)
A) f(-2) = -8/5 and -f(2) = -(8/5) = -8/5. In this case, f(–x) = –f(x) . KEEP
B) f(-2) = 3/5 and -f(2) = -(3/5) = -3/5. In this case, f(–x) ≠ –f(x) . ELIMINATE
C) f(-2) = 12 and -f(2) = -(12) = -12. In this case, f(–x) ≠ –f(x) . ELIMINATE
D) f(-2) = 18 and -f(2) = -(14) = -14. In this case, f(–x) ≠ –f(x) . ELIMINATE
E) f(-2) = -36 and -f(2) = -(28) = -28. In this case, f(–x) ≠ –f(x) . ELIMINATE
By the process of elimination, the correct answer is A
Cheers,
Brent
Hi Brent, is there a quicker way to do this question? Plugging in values took a lot of time.